Risk factors for Ahmed Glaucoma Valve (AGV) Failure in Glaucoma Patients - Yadgari, Maryam; Nilforushan , Naveed; Mahmoudi Nejad Azar , Sahar (Journal of Ophthalmic and Optometric Sciences, 2023)
Background: To investigate the Risk factors for AGV ( Ahmed glaucoma valve) failure. Material and Methods: A retrospective review was conducted on the medical records of patients with varying causes of glaucoma who had undergone AGV implantation. The primary measure of success was the cumulative achievement of an intraocular pressure (IOP) between 5 and 21 mmHg, with a 20 % reduction from baseline, with or without medication to lower IOP. The secondary measures of success were the IOP levels and the number of medications used for glaucoma treatment. Results: The study enrolled a total of 120 participants, with an average age of 48.9 ± 19.6 years and an average follow-up period of 4.5 ± 1.4 years. The mean survival duration was 5.3 ± 0.5 years in patients with high pressure (HP), which was significantly shorter than the 6.4 ± 0.2 years in those without HP. The likelihood of surgical failure increased with higher baseline IOP, with an odds ratio of 1.07 (95 % confidence interval: 1.02-1.12). In a logistic regression model, neovascular glaucoma was the only factor significantly associated with the occurrence of HP, with an odds ratio of 3.14 (95 % confidence interval: 1.2-8.1). Conclusion :Neovascular glaucoma and a Higher Baseline IOP are risk factors for AGV failure.